Comparison of the kinetics of monomeric anthocyanins loss and colour changes in thermally treated blackcurrant, maqui berry and blueberry pulps from Argentina - Busso Casati, Carolina (2017)
Fil: Busso Casati, Carolina. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina